THE EFFECT OF HONEY GIVING TO HEMOGLOBIN LEVEL IN PREGNANT MOTHERS THIRDTRIMESTER WITH ANEMIA AT SUMAJA MAKMUR VILLAGE MUARA ENIM REGENCY IN THE YEAR OF 2022 - ROMADANA HOTIMA; RISZA CHOIRUNISSA; RETNO WIDOWATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Anemia is an important health problem worldwide. The World Health Organization ( World Health Organizatin/WHO ) reports that the prevalence of pregnant women who experience anemia is around 35-75% and is increasing with increasing gestational age . Acacia Crassicarpa honey is often referred to as a drink that can increase hemoglobin levels because of its high iron content. The purpose of this study was to determine the effect of giving honey on the increase in hemoglobin levels of pregnant women in the third trimester with anemia. The research method uses an intervention study with the one group pretest – posttest method. The population in this study were pregnant women in the third trimester with anemia. The sample size is 15 respondents. The statistical test used was the Wilcoxon test with a 95% confidence level. The results showed that the average hemoglobin level before giving honey was 9.4 g/dL , while after giving honey for 15 days the average was 12.6 g/dL. There was a significant effect ( p value 0.000 < 0.05) giving honey on hemoglobin levels of pregnant women with anemia. It can be concluded and the suggestions given are that honey is effective in increasing the Hb levels of pregnant women, it is hoped that after this research ends, various medical parties will socialize pregnant women, especially those suffering from anemia, to regularly consume honey to increase hemoglobin levels of pregnant women.